Development of an instrumented thoracoscopic surgical trainer for objective evaluation of esophageal atresia/tracheoesophageal fistula repair. - Moorhead, Ashton A.; Nair, David; Morison, Chris; Cook, Nicholas J.; Beasley, Spencer W.; Wells, Jonathan M. (Medical & Biological Engineering & Computing, 2020)
Operative repair of complex conditions such as esophageal atresia and tracheoesophageal fistula (EA/TEF) is technically demanding, but few training opportunities exist outside the operating theater for surgeons to attain these skills. Learning them during surgery on actual neonates where the stakes are high, margins for error narrow, and where outcomes are influenced by technical expertise, is problematic. There is an increasing demand for high-fidelity simulation that can objectively measure performance. We developed such a simulator to measure force and motion reliably, allowing quantitative feedback of technical skill. A 3D-printed simulator for thoracoscopic repair of EA/TEF was instrumented with motion and force tracking components. A 3D mouse, inertial measurement unit (IMU), and optical sensor that captured force and motion data in four degrees of freedom (DOF) were calibrated and verified for accuracy. The 3D mouse had low average relative errors of 2.81%, 3.15%, and 6.15% for 0 mm, 10 mm offset in Y, and 10 mm offset in X, respectively. This increased to - 23.5% at an offset of 42 mm. The optical sensors and IMU displayed high precision and accuracy with low SDs and average relative errors, respectively. These parameters can be a useful measurement of performance for thoracoscopic EA/TEF simulation prior to surgery. Graphical abstract Inclusion of sensors into a high-fidelity simulator design can produce quantitative feedback which can be used to objectively asses performance of a technically difficult procedure. As a result, more surgical training can be done prior to operating on actual patients in the operating theater.